Understanding Jesus in the Early Modern Period and Beyond. Across Text and Other Media Journal for Religion, Film and Media - Miriam Benfatto (Journal for Religion, Film and Media, 2019)
This thematic issue seeks to provide a more nuanced and more complicated history of how historical narratives about the life of Jesus were produced and circulated in European culture. The focus on media is one of the most innovative ways to provide such an involved history, pointing to the cultural history of scholarship and the many ways in which societies produce historical representations of theological themes.